Exploring the mechanism of triptolide inhibiting the motility of fibroblast-like synoviocytes in rheumatoid arthritis via RhoA/Rho-associated kinase axis, based on network pharmacology, molecular docking and molecular dynamics simulations - Shen, Jiacheng; Fang, Yuxuan; Xu, Nan; Chen, Hongyi; Zhu, Miao; Li, Dan; Chu, Zewen; Sunagawa, Masataka; Liu, Yanqing; Wang, Haibo; Li, Guoqing (Frontiers in Pharmacology, 2025)
Background and objectiveRheumatoid arthritis (RA) is a chronic autoimmune disease characterized by the hyperproliferation and invasive behavior of rheumatoid arthritis fibroblast-like synoviocytes (RA-FLS), which contributes to the degradation of articular cartilage and bone. Inhibition of RA-FLS proliferation, migration and invasion has become an important therapeutic strategy for RA. Triptolide (TPL), an epoxy diterpene lactone compound from the traditional Chinese medicine Tripterygium wilfordii Hook. f., has significant immunosuppressive and anti-inflammatory effects. However, the specific mechanisms of TPL-regulated effects on RA-FLS cytoskeleton and inhibition of invasive metastasis are not yet fully explored. The aim of this study was to investigate TPL-regulated effects on RA-FLS skeleton and reveal the specific mechanism of TPL-inhibition of RA-FLS migration and invasion.Materials and methodsIn vitro experiments were performed using RA-FLS cell line. Cell motility was evaluated by wound healing assay and Transwell assay as well as high content cell imaging system. Cytoskeletal remodeling was observed by cytoskeletal immunofluorescence staining and transmission electron microscopy (TEM). Network pharmacology predicted the targets of Triptolide. RhoA/Rho-associated kinase signaling pathway was detected by quantitative real-time PCR and Western blotting. Molecular docking and molecular dynamics simulations were used to validate the interaction of Triptolide with RhoA/Rho-associated kinase.ResultsTPL significantly inhibited RA-FLS cell motility, and reduced the displacement and cumulative distance of RA-FLS. Cytoskeleton staining assay and TEM observation showed cytoskeleton remodeling after TPL treatment. Network pharmacological prediction screened 45 targets associated with TPL intervention in RA via cytoskeleton, including TNF, KRAS, ESR1, RHOA, MAPK3 and CASP3. In the RhoA/Rho-associated kinase signaling pathway, TPL treatment inhibited protein expression and phosphorylation of RhoA, Rock, and Limk. TPL can enter RhoA, Rock1, and Rock2 target protein binding domains with stable binding activities, and may cause conformational changes of Rock1 related to molecular functions.ConclusionTPL inhibits RA-FLS in motility by regulating actin cytoskeleton remodeling through action on the RhoA/Rho-associated kinase signaling pathway.